Acoustic emission activity and damage evolution characteristics of marble under triaxial stress at high temperatures - LI Hao-ran; WANG Zi-heng; MENG Shi-rong; ZHAO Wei-gang; CHEN Feng (Rock and Soil Mechanics, 2021)
In order to reveal the fracture development and damage evolution law of marble under the influence of temperature, the deformation and failure characteristics and acoustic emission activity of marble under the conditions of 30, 60, 90, 120 ℃ and 150 ℃ were studied by using triaxial servo testing machine and acoustic emission testing system. The results show that the triaxial compression failure of marble under high temperature goes through four stages: compaction and elastic deformation stage, plastic deformation stage, ductile failure stage and instability failure stage. The higher the test temperature is, the longer the compaction deformation stage and ductile failure stage are, and the rock gradually transforms from elastic brittle failure to elastic-plastic failure. The peak strength, elastic modulus and internal friction angle of marble decrease with the increase of temperature. The acoustic emission activity of rock and the correspondence between AE location and macroscopic crack decrease with the increase of test temperature. By analyzing the characteristics of acoustic emission signal amplitude, impact, ring down count, acoustic emission energy, peak frequency and b value in the damage evolution process of marble, it is found that the amplitude fluctuation of acoustic emission is small and the temperature sensitivity is poor, but the peak frequency and b value parameters can better characterize the crack development inside the rock. The peak frequency has the highest temperature sensitivity, which is favorable as the prediction index of rock failure and instability. In the process of triaxial compression failure, tension-shear composite cracks appear in marble, of which shear cracks are dominant. High temperature inhibits the initiation of internal cracks in rock mass. The higher the test temperature is, the weaker the tensile failure and the stronger the shear failure are. The test results shed light on the study of rock thermal damage mechanism and engineering thermal damage monitoring and prediction.